Symmetry-breaking thermomagnetic dynamics of ferrofluid: Oscillation, spontaneous rotation, and flow bistability under laser irradiation - Chengzhen Qin; Feng Lin; Chong Wang; Suchuan Dong; Zhiming Wang; Jiming Bao (Proceedings of the National Academy of Sciences, 2026)
Fluidic oscillation and flow bistability—classical signatures of nonlinear fluid dynamics—typically occur at high Reynolds numbers, whereas the Rosensweig instability, manifested as spike formation on a ferrofluid surface under a magnetic field, reflects a static nonlinear phenomenon. Here, we report oscillation and bistable rotation of ferrofluid spikes under continuous-wave laser excitation. Enabled by Marangoni instability, local laser heating causes a single spike to vanish or to oscillate around the laser spot like a pendulum. For two or more spikes, the pattern undergoes steady clockwise or counterclockwise rotation, depending on the laser position. A brief puff of air or a gentle drag with a tip in the opposite direction can reverse the rotation direction. These behaviors arise from symmetry breaking and asymmetric thermomagnetic forces. Single spike oscillation results from the breaking of axial symmetry of the magnetic field, whereas multispike rotation occurs even in a perfectly axisymmetric field through spontaneous symmetry breaking of the coupled magnetic-field–ferrofluid–laser system. The two rotation directions constitute bistable states separated by an energy barrier, analogous to deformable mechanical systems that switch states under external perturbations. Our findings provide a simple, reconfigurable platform for exploring nonlinear fluid dynamics at low Reynolds numbers and open opportunities in optofluidics and soft robotics.